Biparietal/transverse abdominal diameter ratio ≤ 1: potential marker for open spina bifida at 11–13‐week scan. (March 2015) - Simon, E. G.; Arthuis, C. J.; Haddad, G.; Bertrand, P.; Perrotin, F.
ABSTRACT Objective In the first trimester of pregnancy, a biparietal diameter (BPD) below the 5th percentile is a simple marker that enables the prenatal detection of half of all cases of open spina bifida. We hypothesized that relating the BPD measurement to the transverse abdominal diameter (TAD) might be another simple and effective screening method. In this study we assessed the performance of using the BPD/TAD ratio during the first trimester of pregnancy in screening for open spina bifida. Methods A total of 20 551 first‐trimester ultrasound scans (11–13 weeks' gestation), performed between 2000 and 2013, were analyzed retrospectively; there were 26 cases of open spina bifida and 17 665 unaffected pregnancies with a crown–rump length of 45–84 mm and a record of both BPD and TAD measurements. Results The mean (± SD) BPD/TAD ratio was 1.00 ± 0.06 for fetuses with spina bifida and 1.13 ± 0.06 for those without (P < 0.0001). A BPD ≤ 5th percentile enabled the prenatal detection of 46.2% of spina bifida cases, while a BPD/TAD ratio of ≤ 1.00 detected 69.2%. If we considered cases in which either BPD was ≤ 5th percentile or BPD/TAD ratio was ≤ 1, we identified 76.9% of cases. In the latter case, the false‐positive rate was 5.1%, while that for using a combination of both BPD ≤ 5th percentile and BPD/TAD ratio ≤ 1 was 0.6%, with a sensitivity of 38.5%. The positive predictive value of using a combination of BPD ≤ 5th percentile and BPD/TAD ratio ≤ 1 for detecting spina bifida was 8.5%. Conclusions Between 11 and 13 weeks' gestation, relating BPD to TAD improves considerably the diagnostic performance of using BPD measurement alone in screening for open spina bifida. Screening using this marker is simple and applicable to a large population. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.